Influencing factors and mechanisms of action on the participation intentions of cryptocurrency investment fraud victims—A quantitative examination from the perspective of the theory of planned behavior - Jianbo Wang; Liang Deng (PLoS ONE, 2026)
With the rise of cryptocurrency, using cryptocurrency investments to conduct fraud has become a common criminal tactic. Drawing on survey data from 287 victims in China, this study explored the determinants and mechanisms of investment intention among victims of cryptocurrency investment scams. Based on the TPB and using SEM, we identified three main findings: (1) Investment attitude and perceived behavioral control have a significant positive impact on victims’ intention to invest. (2) Risk-seeking personality traits, laws and regulations, investment education, and fraud cases exposure not only directly affect this intention but also influence it indirectly through investment attitude and perceived behavioral control. (3) Subjective norms have a limited impact on investment intention. These conclusions suggest a challenge to the traditional TPB. The decentralized nature of cryptocurrency may make victims rely more on personal judgment than social influence. This finding expands the applicability of the TPB. It also provides a basis for developing targeted fraud prevention systems.